CONSUMING BODIES ([S.l.])
1 online resource
Keywords: "Consuming Bodies takes a critical perspective on body commodification both in the US and across the globe, addressing newly emerging practices and making an important contribution to social scientific understandings of the body that goes beyond the Eurocentrism of the extant scholarly literature"--